SUSTAINABLE SUBCONTRACTOR SELECTION IN IRRIGATION PROJECTS: A WEIGHT PRODUCT MULTI-CRITERIA DECISION ANALYSIS - Denny Jean Cross Sihombing (LPPM Universitas Bina Bangsa, 2024)
This research aims to reveal the crucial role of subcontractor selection in irrigation projects, which require water resource management to increase agricultural productivity and ensure adequate water availability. The projects are complex, involving designing efficient water distribution systems, constructing structures such as dams, and tight coordination between various stakeholders. The selection of subcontractors significantly impacts the project's success, affecting critical aspects such as time, quality, and cost. This research applies the Weight Product method as a multi-criteria decision-making approach to prioritize these aspects. The advantage of this method lies in its ability to handle multi-criteria decisions systematically. By modeling this method, this research aims to improve the effectiveness and efficiency of subcontractor selection in irrigation projects. The results are expected to provide directional guidance for the dev developing tractor selection applications to improve the quality of project implementation and r quality due to associated risks